2014
DOI: 10.1099/vir.0.067819-0
|View full text |Cite
|
Sign up to set email alerts
|

Epitope mapping of the 2009 pandemic and the A/Brisbane/59/2007 seasonal (H1N1) influenza virus haemagglutinins using mAbs and escape mutants

Abstract: Research Center in Infectious Diseases of the CHUQ-CHUL and Laval University, Qué bec City, QC, Canada mAbs constitute an important biological tool for influenza virus haemagglutinin (HA) epitope mapping through the generation of escape mutants, which could provide insights into immune evasion mechanisms and may benefit the future development of vaccines. Several influenza A (H1N1) pandemic 2009 (pdm09) HA escape mutants have been recently described. However, the HA antigenic sites of the previous seasonal A/B… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

2
11
1

Year Published

2015
2015
2022
2022

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 15 publications
(14 citation statements)
references
References 41 publications
2
11
1
Order By: Relevance
“…Although our study, and those of others (Rudneva et al, 2012; Chen et al, 2013; Retamal et al, 2014), did not observe this epitope, this highlights the need to further expand our understanding of the antigenicity of H1N1pdm09 HA, beyond that of the classical antigenic mapping of the HA of PR/8 (Caton et al, 1982). This will not only aid our understanding of the protective antibody response against this virus, but will also support surveillance and vaccine candidate selection efforts that monitor viral drift in the human population.…”
Section: Discussioncontrasting
confidence: 83%
“…Although our study, and those of others (Rudneva et al, 2012; Chen et al, 2013; Retamal et al, 2014), did not observe this epitope, this highlights the need to further expand our understanding of the antigenicity of H1N1pdm09 HA, beyond that of the classical antigenic mapping of the HA of PR/8 (Caton et al, 1982). This will not only aid our understanding of the protective antibody response against this virus, but will also support surveillance and vaccine candidate selection efforts that monitor viral drift in the human population.…”
Section: Discussioncontrasting
confidence: 83%
“…To ensure the loss of antigenicity for an individual antigenic site, each mutant virus in our panel contained 5 or more amino acid substitutions within 1 antigenic site. Additionally, several amino acid substitutions that were included in our panel were consistent with previously described escape mutations (18). While our study focused on the classically defined epitopes of pandemic H1 hemag glutinin, several nonclassical epitopes have been described as being HI sensitive (11,19,20).…”
Section: Resultsmentioning
confidence: 55%
“…These low-impact substitutions are common in the evolution of IAVs and are useful for tracking antigenic evolution 50 . The amino acid substitution G155E has been previously reported as causing a high-impact antigenic change in A(H1N1)pdm09 IAVs 44,45,55,56 . This substitution is analogous to the substitution G158E, which is responsible for major antigenic changes during evolution of H3N2 IAVs 51 .…”
Section: Discussionmentioning
confidence: 97%
“…Nevertheless, we found a high antigenic variability within the Chilean A(H1N1)pdm09-like cluster and some Chilean strains had additional glycosylation sites in or near the antigenic site Sa. This site is one of the most variable antigenic sites among Chilean A(H1N1)pdm09-like viruses, which has been shown to be important for the antigenic evolution of A(H1N1)pdm09-like viruses [42][43][44][45] . Of interest, previously it has been shown that most of glycosylation sites acquired in H1 viruses from 1918 to 2009 have been located in or near antigenic site Sa 20 .…”
Section: Discussionmentioning
confidence: 99%